Financial health and firm productivity: Firm-level evidence from Viet Nam - Shandre M. Thangavelu; Aekapol Chongvilaivan (Asian Development Bank Institute (ADBI), 2013)
Does financial health shore up firm productivity? This paper empirically investigates this question and presents productivity as another driving factor in translating financial development into real economic progress. Our empirical framework employs Levinsohn and Petrin's (2003) semi-parametric estimation of total factor productivity (TFP) using firm-level panel data during 2002 - 2008, and incorporates financial health variables into conventional determinants of firm productivity. Our findings suggest that liquidity and access to external credit boosts firm productivity, with the latter particularly imperative for exporting and/or importing firms. We also present supplementary results regarding economies of scale, high-tech capital accumulation, human capital investment and foreign ownership.
Keywords: O16; O25; O53; 330; financial health; total factor productivity; financial development; Wirtschaftlichkeit; Produktivität; Unternehmenserfolg; Außenhandel; Panelforschung; Vietnam